(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The hypothesis tested was that grasses belonging to the same species, but with variations in forage canopy architecture, would not present oscillations in the variables related to primary production, nutritional value and animal performance under similar edaphoclimatic conditions under the same management system. Thus, the present work intends to evaluate the different cultivars of Brachiaria brizantha observing the dissimilarity of the variables related to forage biomass, nutritive value and animal performance. The experiment was conducted by the Empresa Brasileira de Pesquisa Agropecuária. The design was completely randomized blocks with three replicates. The treatments were three ecotypes of Brachiaria brizantha, B4, BRS Paiaguás and Xaraés. The grazing method used was the intermittent variable stocking rate. The data of forage canopy height, population density of tillers and index of leaf area were submitted analysis of variance. Estimates of the first and second canonical variables, as well as standardized canonical coefficients were performed. It was noticed oscillations at the height of the foraging canopy between the grasses, in which, pastures of Ecotype B4 present the highest height in relation to the other B. brizantha. BRS Paiaguás presents the highest population density of tillers. The standard canonical coefficients of the first canonical variable showed that net detergent fiber and Lignin are the variables that most affect the first canonical variable, positively and negatively. This indicates that these are the variables that most interfere in the differentiation of characteristics related to the nutritive value of B. brizantha grasses. The first canonical variable explains 80.5% of the B. brizantha pasture variation, in addition, it is possible to observe a differentiated distribution among the pastures studied. The B. brizantha pastures present variations in forage canopy architecture, which end up impacted by the canopy lignin concentration.